Specialized medical care for patients with malignant neoplasms of the maxillofacial area in the Penza region of Russia - M. V. Lebedev; Yu. A. Abdullina; I. Yu. Zakharova (Biomedical Photonics, 2021)
This article analyzes domestic and foreign sources, regulatory documents of the Russian Federation, in order to determine the etiological factors of oral cancer, assess the statistical data on morbidity and mortality from malignant neoplasms of the maxillofacial region in the Penza region. The results of changing the routing, an interdisciplinary approach to treating patients with malignant neoplasms of the maxillofacial region in the Penza region are presented. The epidemiology, clinical manifestations, main diagnostic methods, routing, treatment and rehabilitation of patients with head and neck oncology are considered. The results of treatment of patients with oral cavity and lower lip cancer using photodynamic therapy (PDT), both alone and in combination with radiation and chemotherapy, are analyzed. The study showed that PDT of tumors of the lower lip and buccal mucosa in mono-mode made allowed achieving 100% efficiency. After the completed treatment, all participants in the experiment were provided with a complex of rehabilitation, including nutritional support, psychological assistance, exercise therapy, training in correct swallowing tactics, percutaneous endoscopic gastrostomy, and a course of oral cavity massage. An interdisciplinary approach to treating malignant neoplasms of the maxillofacial region is the most correct in modern practice.